ENHANCING ENGLISH VOCABULARY AMONG STUDENTS WITH INTELLECTUAL DISABILITIES THROUGH FLASHCARD-BASED INSTRUCTION - Sudiro, Suryo; Abdul Karim, Sayit; Nur Fadillah, Laely; Nur Istiqomah, Annisa; Nur Hasanah, Reni; Matas, Gordan (English Review: Journal of English Education, 2025)
Vocabulary acquisition is fundamental to English language fluency, enabling comprehension in reading and listening, which subsequently facilitates speaking proficiency. Flashcards offer an engaging learning medium for vocabulary development, particularly beneficial for students with intellectual disabilities who often experience boredom and disinterest in traditional English instruction. This study investigated the effectiveness of flashcards intervention in enhancing vocabulary mastery of nine students with intellectual disabilities enrolled at SLB Rela Bhakti II Wates, Yogyakarta. Employing a pre-experimental, one group pre-test-post-test research design with a quantitative approach, assessed vocabulary gains following the flashcard-based intervention. The pretest established baseline vocabulary knowledge, followed by targeted flashcard instruction, and concluded with a posttest to measure improvement. Data analysis compared pretest and posttest scores to determine the impact of the intervention. The results of the study demonstrated a significant increase in vocabulary mastery. The average pretest score was 6, while the average posttest score rose to 44.4. Furthermore, the lowest pretest score was 0, increasing to 26 in the posttest, and the highest pretest score of 32 improved to 76 in the posttest, indicating substantial vocabulary growth across all participants. These findings suggest that flashcards are an effective tool for improving speaking vocabulary among students with intellectual disabilities.